2019
DOI: 10.2136/vzj2019.05.0053
|View full text |Cite
|
Sign up to set email alerts
|

Can Drip Irrigation be Scheduled with Cosmic‐Ray Neutron Sensing?

Abstract: Cosmic‐ray neutron sensing (CRNS) was used in a drip‐irrigated field. Soil water content was estimated from CRNS. Neutron transport was simulated for the drip‐irrigated field. CRNS has limitations for irrigation scheduling of drip‐irrigated fields. Irrigation is essential for maintaining food production in water‐scarce regions. The irrigation need depends on the water content of the soil, which we measured with the novel technique of cosmic‐ray neutron sensing (CRNS). The potential of the CRNS technique for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…In general, calibration (RMSE: 0.013 and 0.007 m 3 m −3 for T and C plots, respectively) and validation (KGE: 0.84 and 0.75 for T and C plots, respectively) procedures showed values that indicate a good performance of CRNP, which in the case of the non-thinned forest (C-plot), improved with the application of the vegetation correction factor. These values are comparable to those obtained in other studies such as that of Bogena et al (2013); they obtained a RMSE value of 0.025 m 3 m −3 for a forested area, and Li et al (2019), who found a RMSE value of 0.025 m 3 m −3 for a semi-arid environment, or Lv et al (2014), who found RMSE values varying between 0.011 and 0.023 m 3 m −3 for a humid forest (gross precipitation of 950 mm y −1 ). However, when comparing O CRNP to O g , there is a general overestimation by CRNP that can be attributed to the influence of biomass and the different measurement depths of both methodologies and changes under the different subperiods ( Figure 5).…”
Section: Discussionsupporting
confidence: 90%
“…In general, calibration (RMSE: 0.013 and 0.007 m 3 m −3 for T and C plots, respectively) and validation (KGE: 0.84 and 0.75 for T and C plots, respectively) procedures showed values that indicate a good performance of CRNP, which in the case of the non-thinned forest (C-plot), improved with the application of the vegetation correction factor. These values are comparable to those obtained in other studies such as that of Bogena et al (2013); they obtained a RMSE value of 0.025 m 3 m −3 for a forested area, and Li et al (2019), who found a RMSE value of 0.025 m 3 m −3 for a semi-arid environment, or Lv et al (2014), who found RMSE values varying between 0.011 and 0.023 m 3 m −3 for a humid forest (gross precipitation of 950 mm y −1 ). However, when comparing O CRNP to O g , there is a general overestimation by CRNP that can be attributed to the influence of biomass and the different measurement depths of both methodologies and changes under the different subperiods ( Figure 5).…”
Section: Discussionsupporting
confidence: 90%
“…It uses the validated near-ground cosmic-ray neutron spectrum by Sato (2016). The code was employed for CRNS footprint revision by Köhli et al (2015) and Schrön et al (2017), in roving (Schrön et al, 2018) and irrigation studies (Li et al, 2019) as well as understanding the signal for snow height measurements (Schattan et al, 2019). It also features special input options for conducting detector-related neutron transport studies (Köhli et al, 2018).…”
Section: Uranosmentioning
confidence: 99%
“…Mobile campaigns have also extended the spatial scale up to several km 2 and therefore could contribute to closing the measurement scale gap, especially relevant for small catchments (Schrön et al, 2018). Furthermore, CRNS has shown to be a prominent candidate for agricultural applications (Franz et al, 2016;Li et al, 2019), for validation of satellite based measurements (Montzka et al, 2017) and to improve hydrological modeling (Shuttleworth et al, 2013). The success of this technique (Andreasen et al, 2017) lead to a worldwide deployment of meanwhile more than 100 sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Common approaches for developing and improving irriga-tion management include calculating crop water requirements (e.g., [62]), monitoring soil water status (e.g., [63,64]), combining soil water balancing and soil sensing (e.g., [65,66]), and monitoring canopy temperature (e.g., [67,68]). Also, an experimental approach involving cosmic-ray neutron sensing for drip irrigation scheduling can be found in recent literature [69]. The overall objective of these studies is to maximise water productivity, which can be achieved by increasing irrigation efficiency (reducing unproductive losses) and at the same time stabilising yield.…”
Section: Subirrigationmentioning
confidence: 99%